Joanne Rappaport, The Disappearing Mestizo. Configuring Difference in the Colonial New Kingdom of Granada (Durham and London: Duke University Press, 2014), 352 pp. (2015)
Reseña de Joanne Rappaport, The Disappearing Mestizo. Configuring Difference in the Colonial New Kingdom of Granada (Durham and London: Duke University Press, 2014), 352 pp.